2017
DOI: 10.1101/171454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable neural mechanisms track evidence accumulation for selection of attention versus action

Abstract: Decision-making is typically studied as a sequential process from the selection of what to attend (e.g., between possible tasks, stimuli, or stimulus attributes) to the selection of which actions to take based on the attended information. However, people often gather information across these levels in parallel. For instance, even as they choose their actions, they may continue to evaluate how much to attend other tasks or dimensions of information within a task. We scanned participants while they made such par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
(102 reference statements)
3
11
0
Order By: Relevance
“…ACC information signals changed several hundred milliseconds before gaze shifts, while BG signals changed more proximally to behavior. This finding supports and extends theories that ACC is especially important for motivating behavioral shifts to explore available prospects and learn their reward value and other properties [61][62][63] , tracking their level of uncertainty and how it evolves over time as beliefs are updated in response to surprising outcomes 12,62,[64][65][66][67][68] , and using this information to decide how to control future cognition and behavior 62,69 . In particular, while it is well acknowledged that the ACC needs to receive a broad array of reward-and uncertainty-related information to perform these functions 62,69 , our data indicates that the ACC is not a mere passive recipient of this information; rather, the ACC is tightly linked to the emergence of motivational drive to actively seek out that information from the environment.…”
Section: Anterior Cingulate Cortex and Information Seeking Behaviorsupporting
confidence: 80%
“…ACC information signals changed several hundred milliseconds before gaze shifts, while BG signals changed more proximally to behavior. This finding supports and extends theories that ACC is especially important for motivating behavioral shifts to explore available prospects and learn their reward value and other properties [61][62][63] , tracking their level of uncertainty and how it evolves over time as beliefs are updated in response to surprising outcomes 12,62,[64][65][66][67][68] , and using this information to decide how to control future cognition and behavior 62,69 . In particular, while it is well acknowledged that the ACC needs to receive a broad array of reward-and uncertainty-related information to perform these functions 62,69 , our data indicates that the ACC is not a mere passive recipient of this information; rather, the ACC is tightly linked to the emergence of motivational drive to actively seek out that information from the environment.…”
Section: Anterior Cingulate Cortex and Information Seeking Behaviorsupporting
confidence: 80%
“…In addition to the frontoparietal activations, the dorsal anterior cingulate cortex (dACC) and insula were also more active on Motivation Consistent trials. The dACC and insula are part of a salience network involved in the detection of motivationally salient stimuli 40,41 , and the dACC has been recently implicated in determining what stimulus feature to attend to in a perceptual decision-making task 42 . The increased activity in the salience network on Motivation Consistent trials might be responsible for the selection of motivationally relevant features for enhanced processing.…”
Section: Discussionmentioning
confidence: 99%
“…The HRL-ACC model applies a similar division of labor to the domain of action selection: dorsal areas of ACC, which are closely linked to motor behavior, control performance over specific tasks (e.g., climbing a barrier in a maze), whereas rostral areas of ACC control the execution of higherlevel options (e.g., switching between egocentric and allocentric navigation strategies) [15]. Recent support for this idea comes from fMRI studies revealing that dACC is sensitive to reward values corresponding to overt gains whereas rACC is more sensitive to higher-level goals [46], and that dACC accumulates evidence about how best to respond in a task whereas rACC accumulates evidence about what task strategy to deploy [47]. Further, a recent study that recorded the intracranial electroencephalogram in humans revealed that rACC determines the set point at which the agent switches between action plans and dACC utilizes feedback to determine whether to continue with or switch between the plans according to that set point [48].…”
Section: Neural Implementationmentioning
confidence: 99%